1982
DOI: 10.1073/pnas.79.3.795
|View full text |Cite
|
Sign up to set email alerts
|

DNA stimulates ATP-dependent proteolysis and protein-dependent ATPase activity of protease La from Escherichia coli.

Abstract: The product of the Ion gene in Escherichia coli is an ATP-dependent protease, protease La, that also binds strongly to DNA. Addition of double-stranded or single-stranded DNA to the protease in the presence ofATP was found to stimulate the hydrolysis of casein or globin 2-to 7-fold, depending on the DNA concentration. Native DNA from several sources (plasmid pBR322, phage T7, or calf thymus) had similar effects, but after denaturation the DNA was 20-100% more effective than the native form. Although poly(rA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…Different observations have been reported for the relationship between DNA binding and the enzymatic activities of bacterial Lon (51,53,54,56). One study showed that large DNA molecules such as plasmid, bacteriophage and calf thymus DNA stimulate the ATPase and protease activities of Lon (51). By contrast, another study observed that DNA stimulated ATP hydrolysis but inhibited proteolysis (53).…”
Section: Lon As a Dna Binding Proteinmentioning
confidence: 95%
See 2 more Smart Citations
“…Different observations have been reported for the relationship between DNA binding and the enzymatic activities of bacterial Lon (51,53,54,56). One study showed that large DNA molecules such as plasmid, bacteriophage and calf thymus DNA stimulate the ATPase and protease activities of Lon (51). By contrast, another study observed that DNA stimulated ATP hydrolysis but inhibited proteolysis (53).…”
Section: Lon As a Dna Binding Proteinmentioning
confidence: 95%
“…The SSD sub-region of the ATPase domain of B. thermoruber Lon is sufficient for DNA binding (55), whereas the ATPase domain lacking the SSD of EcLon also binds DNA (54). Different observations have been reported for the relationship between DNA binding and the enzymatic activities of bacterial Lon (51,53,54,56). One study showed that large DNA molecules such as plasmid, bacteriophage and calf thymus DNA stimulate the ATPase and protease activities of Lon (51).…”
Section: Lon As a Dna Binding Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17) Lon and two other proteases (ClpAP and ClpXP) are responsible for 70% to 80% of the energy-dependent protein degradation in E. coli. 5) We found that mutations in both the Lon and Clp proteases produce the same phenotype as ppk mutations and that the addition of amino acids overcomes the block in these cases.…”
Section: Polyp-lon Complex: a Missing Link Between The Stringent mentioning
confidence: 99%
“…Some results show that addition of DNA enhances ATP hydrolysis and that protease La apparently binds to DNA. It is possible that the binding of La to DNA has a significant influence on regulation of degradation of proteins (Chung and Goldberg, 1982).…”
Section: Introductionmentioning
confidence: 99%